DESAIN APLIKASI SMS GATEWAY SEBAGAI SISTEM LAYANAN MENERAPKAN METODE STORE AND FORWARD PADA PT. FASTRONIC MAKMUR SENTOSA SEMARANG - Siswanto Siswanto; Sarwo Nugroho (Pixel :Jurnal Ilmiah Komputer Grafis, 2019)
PT Fastronic Makmur Sentosa (FMS) is an Authorized Dealer Smartfren which distributes products from Smartfren, like Staterpack prime, vouchers, modems and handsets doungle bandling. SMS Gateway application as a service functioned to integrate systems between customers with automated information systems, the customer service with the administration in order to obtain valid information. Customers can order products and access information easily via SMS without having to come directly to the PT. FMS information regarding pricing, promotion information, product specifications and ordering products for customers who are already registered. SMS Gateway application can also help customer service in its duty to serve customers with data that is clear and ter updates can be seen in the administration module. With the SMS Gateway Application to deliver information more quickly when customers need information, generate reports on the stock with a clear to the administration